Centella Methodist Church. - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows the Centella Methodist Church with church goers in front of the building. Centella Methodist Church, evolved from a Mission Sunday School sponsored by First Methodist Church. Centella Methodist Church no longer exists as it was combined with St. Paul Methodist Church over fifty years ago. The church's name became St. Paul's Methodist Church after the two churches combined.